Review: GOURINAT, Jean-Baptiste (dir.). L’étique du stoïcien Hiéroclès. Villeneuve d’Ascq: Presses Universitaires du Septentrion, 2016. Pp. 175.ISBN 978-2-7574-1273-2.EUR 22,00. - Brito, Rodrigo Pinto de (Rónai – Revista de Estudos Clássicos e Tradutórios, 2017)
No abstract since it is a review...